Estudio piloto de un Programa Deportivo Breve basado en Compasión y ACT en la selección Portuguesa de balonmano femenino (u18) - Carraça, Bruno; Magalhães, Catia (Retos, 2025)
Introduction: Programs based on contextual-behavioural therapies have been developed for application in the sports context to promote attention to the present moment, and the acceptance of internal states in a non-judgmental and compassionate way during the last two decades. Objective: Analyse the results of a pilot sport-compassion contextual-behavioural program for female young athletes (Portuguese National U18 handball team) by assessing state self-compassion and mindfulness on sport satisfaction, stress competition, coach leadership, and sport psychological skills measures before and after the intervention. Methodology: BCOMP.ACT Program is a new semi-structured integrative intervention based on sport-compassion contextual-behavioural approach. The main four- session intervention taught the basics of mindfulness, compassion, and psychological flexibility. Participants completed validated surveys before and after the intervention. Results: After the intervention, participants reported improvement in mindfulness ability, t(18) = 5.20, p<.05, self-compassion, psychological competencies t(18)= -9.25, p<.05 ; coach satisfaction t (18)= -3.45; p<.05; and decrease in competition stress t(18)=8.98; p<.05; injuries fear t(18)= 12.63; p<.05. Discussion: in line with existing research, which has shown the emerging evidence and positive results that suggest that interventions based on contextual-behavioural therapies (eg.,mindfulness, compassion and psychological flexibility) can support and improve mental health and performance in athletes and decrease toxic stress and injuries Conclusions: These findings indicate a potential benefit of short programs based on this type of approach, as BCOMP.ACT, for improving mindfulness, self-compassion, and psychological flexibility in teen’s female athletes.